Biotic and abiotic controls on sediment carbon dioxide and methane fluxes under short-term experimental warming. (1st November 2022) - Lü, Weiwei; Ren, Haoyu; Ding, Wanchang; Li, He; Yao, Xin; Jiang, Xia; Qadeer, Abdul
Highlights: Sediment CO2 fluxes were more sensitive than CH4 fluxes under warming. Dissolved oxygen was the predominant factor of sediment temperature-dependent CO2 flux variation. Methanococcales were the key predictor of sediment temperature-dependent CH4 flux variation. Abstract: Due to the differences in biotic and abiotic factors between soil and sediments, the predicted linkages between biotic and abiotic factors and soil carbon dioxide (CO2 ) and methane (CH4 ) fluxes under warming may not be suitable for sediments. Additionally, the combination of biotic and abiotic factors which determines sediment temperature-dependent CO2 and CH4 fluxes remains unresolved. To address this issue, different types of sediments (including lake, small river and pond sediments) collected from 30 sites across the Yangtze River Basin were incubated under short-term experimental warming. During the incubating phase, the sediment temperature-dependent CO2 and CH4 fluxes as well as the accompanying biotic factors (organic carbon and microbial community) and abiotic factors (pH and dissolved oxygen (DO)) were determined and analyzed synthetically. Our results indicated that sediment CO2 fluxes were more sensitive than CH4 fluxes to warming, which might lead to a relatively large CO2 contribution to total greenhouse gas emissions in a warming climate. Additionally, temperature-dependent CO2 fluxes in pond sediments were more sensitive than those in lake sediments. Random forest analysis indicated that DO greatly affected the variation in the sediment temperature-dependent CO2 fluxes, whereas Methanococcales primarily predicted the CH4 fluxes under warming. DO also highly affected the variation in the temperature sensitivity of CH4 fluxes, whereas pH mostly predicted the temperature sensitivity of CO2 fluxes. Our findings suggest that biotic and abiotic factors, especially DO, pH and the composition of methanogens, coregulate CO2 and CH4 emissions in response to climate warming. Therefore, biotic and abiotic factors should be considered in the models for predication and investigation of sediment organic carbon dynamics under climate change. Graphical abstract: Image, graphical abstract